Edu-Eco Kreasi Disabilitas Mandiri Melalui Inovasi Batok Kelapa Pada Anggota Himpunan Wanita Disabilitas Indonesia HWDI Kabupaten Kudus - Ahmat Fatoni Rizal; Henry Suryo Bintoro; Devi Puji Lestari; Lia Permata Sari; Ilham Fajar Sidqi (Muria Jurnal Layanan Masyarakat, 2021)
HWDI (Indonesian Women with Disabilities Association) Kudus Regency is a community for women with disabilities located in the holy city. The problem faced is that women with disabilities have difficulty taking care of themselves, especially getting a job. Indonesia produces 3 million tonnes of coconut per year. Coconut shell waste is 360 thousand tons per year (quoted from Kagama.Co, Bulaksumur). If this condition is allowed, the waste will continue to mount, which of course will trigger environmental pollution and health problems. One of the roles of overcoming this condition is by recycling coconut shell waste and processing it into handicraft products that can be used again and even have high economic value. Through this activity the PKM team conducted training on making handicraft products by utilizing coconut shell waste, marketing training for the handicraft products produced and empowering marketing and mentoring for the sale of handicraft products to HWDI members.